2020
DOI: 10.1039/c9ra09119j
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-flow synthesis of dimethyl fumarate: a powerful small molecule for the treatment of psoriasis and multiple sclerosis

Abstract: Dimethyl fumarate (DMF) has recently gained attention due to its use as a pro-drug in different pharmaceutical preparations, here in we present our work on a cascade methodology in short reaction times and quantitative yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…De Souza and colleagues reported a continuous flow process for the preparation of dimethyl fumarate, an API for treating psoriasis and multiple sclerosis. 876 The process relied on the Fischer esterification of fumaric acid with methanol, catalyzed by sulfuric acid. 98% yield was obtained in flow under optimized conditions, corresponding to 10.2 kg day −1 productivity.…”
Section: Upgrading Of Carboxylic Acidsmentioning
confidence: 99%
“…De Souza and colleagues reported a continuous flow process for the preparation of dimethyl fumarate, an API for treating psoriasis and multiple sclerosis. 876 The process relied on the Fischer esterification of fumaric acid with methanol, catalyzed by sulfuric acid. 98% yield was obtained in flow under optimized conditions, corresponding to 10.2 kg day −1 productivity.…”
Section: Upgrading Of Carboxylic Acidsmentioning
confidence: 99%
“…Most recently, de Souza and co-workers [37] reported two continuous flow synthesis strategies of dimethyl fumarate 54 (Figs. 26 and 27), a prodrug used in the treatment of psoriasis and multiple sclerosis.…”
Section: Dimethyl Fumaratementioning
confidence: 99%
“…26 and 27), a prodrug used in the treatment of psoriasis and multiple sclerosis. The prices of treating multiple sclerosis are high reaching 75,000 USD/annum for 87 g dimethyl fumarate (862 USD/g) [37] thus inaccessible to most patients in developing economies. The authors demonstrated two strategies towards dimethyl fumarate starting from either fumaric acid or maleic anhydride.…”
Section: Dimethyl Fumaratementioning
confidence: 99%
“…Over time, different strategies were developed for the production of DMF, exploiting different catalysts, in some cases using different raw materials ( e . g ., maleic anhydride) and also using the CF technology. , In most cases, these alternative strategies do not fully address the reported drawbacks and their actual industrial advantage can be considered really limited.…”
Section: Introductionmentioning
confidence: 99%